2020
DOI: 10.1111/inm.12767
|View full text |Cite
|
Sign up to set email alerts
|

Supporting mental health staff following exposure to occupational violence – staff perceptions of ‘peer’ support

Abstract: Mental health professionals frequently work in environments where stressful, unpredictable, and potentially volatile situations can arise. Staff responses to these, often violent events, can be severe and enduring. Psychological first aid provided by a colleague following exposure to such violence is gaining increasing acceptance as a means of assisting affected individuals. However, there has been little attention to how staff perceive this support. In this study, interviews were conducted with 13 staff emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…While non-Italian reports have sometimes denounced the exposure to violence of MHWs, 28 in our sample there are no statistically significant differences in the need for staff security between the two samples compared. This perception of safety, or at least this not highlighted alarm for insecurity of MHWs in community care in Italy, might be a determining factor for these results.…”
Section: Discussioncontrasting
confidence: 71%
“…While non-Italian reports have sometimes denounced the exposure to violence of MHWs, 28 in our sample there are no statistically significant differences in the need for staff security between the two samples compared. This perception of safety, or at least this not highlighted alarm for insecurity of MHWs in community care in Italy, might be a determining factor for these results.…”
Section: Discussioncontrasting
confidence: 71%
“…The 12 included studies reported individual outcomes from a PFA or a PFA‐based intervention; no studies reported community outcomes. Five studies were randomized control trials (Despeaux et al., 2019; Everly et al., 2016; McCart et al., 2020; Meir et al., 2012) or randomized trials (Ironson et al., 2020); study assignment was not randomized for most: One study was a pilot quasi‐experiment (Ramirez et al., 2013), two were convenience sample pretest–posttest group designs (Cain et al., 2010; Kameno et al., 2021), one was a convenience sample uncontrolled longitudinal design (Blake et al., 2020), one was a qualitative comparative analysis (Schafer et al., 2016), and two were qualitative thematic analyses (Bakes‐Denman et al., 2021; De Freitas Girardi et al., 2020). Four studies had control groups (Despeaux et al., 2019; Everly et al., 2016; McCart et al., 2020; Meir et al., 2012), and five included randomization with regard to the intervention condition (Despeaux et al., 2019; Everly et al., 2016; Ironson et al., 2020; McCart et al., 2020; Meir et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were primarily conducted in the United States (Cain et al., 2010; Despeaux et al., 2019; Everly et al., 2016; Ironson et al., 2020; McCart et al., 2020; Ramirez et al., 2013). Interventions were conducted in school or university facilities (Cain et al., 2010; Despeaux et al., 2019; Everly et al., 2016; Meir et al., 2012; Ramirez et al., 2013), hospitals or other health care settings (Bakes‐Denman et al., 2021; Blake et al., 2020; Kameno et al., 2021), designated child‐friendly spaces (Schafer et al., 2016), community settings (Ironson et al., 2020; McCart et al., 2020), or during home visits (Cain et al., 2010; De Freitas Girardi et al., 2020; Schafer et al., 2016). The target populations were adults (Bakes‐Denman et al., 2021; Blake et al., 2020; Everly et al., 2016; Ironson et al., 2020; Kameno et al., 2021; Schafer et al., 2016), undergraduate college students (Despeaux et al., 2019), adolescents (Ramirez et al., 2013; Schafer et al., 2016), and children (Cain et al., 2010; De Freitas Girardi et al., 2020; Meir et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations